The Drama Studies at the National School of Music: Matilde Díez and Teodora Lamadrid (1874-1896) - Soria Tomás, Guadalupe (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
This paper focuses on the reopened Drama Studies at the National School of Music in 1874. For the first time, women were appointed teachers of Acting. The Government chose the best stage actresses of the time: Matilde Díez and Teodora Lamadrid. We will consider the difficulties they had to overcome to teach their lessons, the plays they rehearsed and the treatise on acting with which the disciples developed their skills. This treatise meant for the scenic realism and was especially attentive to the voice. We will also study how these lessons, one of the few training options for women in the XIX century, improved the public imagen of these teachers.
Keywords: drama training; National School of Music and Drama; Spanish actresses; Matilde Díez; Teodora Lamadrid; female education; Theatre in Nineteenth-century Spain